AB1373 A very high prevalence of vitamin D inadequacy combined with low dietary calcium intake is found in european postmenopausal women. (23rd January 2014) - Bruyere, O.; Buckinx, F.; Reginster, J.-Y.
Abstract : Background: A lack of calcium intake and a low vitamin D level represent a risk factor for osteoporosis. The recommended nutritional intake of calcium is equal to 800 mg/day for European adults but increases to a minimum of 1000 mg/day in women after menopause. The WHO recommends 1300 mg/day for European menopausal women. There are no clear international agreements on what constitutes a level of vitamin D inadequacy, but recent publications suggest that the circulating level of vitamin D should be over 80 nmol/L or at least between 50 nmol/L and 80 nmol/L. Objectives: The objective of this study was to assess the prevalence of low calcium dietary intake combined with low vitamin D level in European postmenopausal osteoporotic women. Methods: The assessment of calcium dietary intake with a validated self-questionnaire and of 25-hydroxyvitamin D [25(OH)D] with a commercial radioimmunoassay (DiaSorin) was performed in 8532 osteoporotic European women from 9 European countries (i.e. Belgium, Denmark, France, Germany, Hungary, Italy, Poland, Spain, United Kingdom). Results: Mean age of the women was 74.2 (7.1) years with a body mass index of 25.7 (4.2) kg/m 2 . The level of 25(OH)D was 61.0 (27.2) nmol/L and the mean calcium dietary intake was 930.7 (±422.9) mg/day. Surprisingly, only 108 out of the 8532 patients (=1.18%) included in this study have a calcium intake superior to 1300 mg and a 25(OH)D level superior to 80 nmol/L. This prevalence only increase to 27.1% when minimal cut-off levels of 800mg of calcium and 50 nmol/L of vitamin D are considered. Conclusions: Calcium dietary intake and vitamin D level are very low in European postmenopausal women. A greater awareness is needed to resolve this public health problem. Disclosure of Interest: None Declared